2023
DOI: 10.3390/su15119112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Remote Sensing and Reanalysis Products for Global Soil Moisture Characteristics

Peng Zhang,
Hongbo Yu,
Yibo Gao
et al.

Abstract: Soil moisture (SM) exists at the land-atmosphere interface and serves as a key driving variable that affects global water balance and vegetation growth. Its importance in climate and earth system studies necessitates a comprehensive evaluation and comparison of mainstream global remote sensing/reanalysis SM products. In this study, we conducted a thorough verification of ten global remote sensing/reanalysis SM products: SMAP DCA, SMAP SCA-H, SMAP SCA-V, SMAP-IB, SMOS IC, SMOS L3, LPRM_C1, LPRM_C2, LPRM_X, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Through a comparison of in situ data and satellite data using multiple indicators, they found that the data's ubRMSE closely approached the product's mission requirement of 0.04 (cm 3 /cm 3 ). Moreover, Zhang et al [25] evaluated the global spatiotemporal accuracy characteristics of SMAP satellite soil moisture based on international ground-based soil moisture observations. The results indicated a high level of accuracy for the SMAP satellite soil moisture product.…”
Section: Introductionmentioning
confidence: 99%
“…Through a comparison of in situ data and satellite data using multiple indicators, they found that the data's ubRMSE closely approached the product's mission requirement of 0.04 (cm 3 /cm 3 ). Moreover, Zhang et al [25] evaluated the global spatiotemporal accuracy characteristics of SMAP satellite soil moisture based on international ground-based soil moisture observations. The results indicated a high level of accuracy for the SMAP satellite soil moisture product.…”
Section: Introductionmentioning
confidence: 99%